Pengaruh Kualitas Pelayanan terhadap Kepuasan, Nilai, Kepercayaan dan Loyalitas Pelanggan Rumah Tangga (Perusahaan Daerah Air Minum Kota Kendari) - Awaluddin, Ishak; Setiawan, Margono (Universitas Brawijaya, Indonesia, 2012)
This study aims to determine the effect of service quality on customer loyalty mediated by Customer satisfaction and customer value eddition, it also examines, the effect of service quality on customersatisfaction, which is mediated by the effect of customer value and customer satisfaction and customer value on customer loyalty mediated by trust. The population in this study are household customers in Kendari who use the services of PDAM for 17,607 households spread are over 9 (nine) districts. The samples in this study are 391 household customers are taken with a precision of 5%. Data collection techniques utilittes questionare. Data are analized by using . Structural Equation Modeling (SEM) with the help of the program. Some of the important findings in this study are: (1) better service improvement of Kendari Regional Water Company (PDAM) will improve customer satisfaction which in turnenhance loyalty if the satisfactioncauses trust. (2) customer loyalty improvement is also achievable if the provided service is able to enhance customer value. Besides, this research also proves that trust has mediating role between satisfaction andloyalty of are customers as well as between customer value and loyalty.